Science Mapping Research on Career Guidance for Junior High School Students: A Bibliometric Analysis from Scopus Database (2019–2025) - Laila Purwaningsih; Abna Hidayati; Jasrial Jasrial; Rahmi Pratiwi; Anggi Prasetia (Yayasan Darussalam Bengkulu, 2026)
Global social changes, the intensive digitalization of educational practices following the COVID-19 pandemic, and the increasing demand for student readiness for professional careers have substantially driven the advancement of career guidance (CG) research. This scientific inquiry seeks to describe the epistemological framework, developmental trajectories, and scientific dynamics of career guidance research using a bibliometric methodology grounded in science mapping techniques. The investigation uses Scopus-indexed publications from 2019 to 2025, which are analyzed using quantitative bibliometric methods and network visualization facilitated by VOSviewer software. The analysis reveals that CG publications exhibit an S-shaped logistic growth pattern, suggesting an early acceleration phase. Publication rates were modest from 2019 to 2021 but surged sharply from 2022 to 2025, driven by growing global interest in technology-based career guidance services. Citation analysis indicates that scientific impact peaked in 2022, with the subsequent decline attributed to a citation lag rather than a decline in research quality. Projections indicate a saturation point of approximately 4,020 documents, with peak production anticipated at approximately 180 publications annually in 2035. The dataset comprises 34,476 references, highlighting the strong theoretical foundations of the CG field and its multidisciplinary scope. Thematic mapping illustrates three main categories: psychological dimensions of counseling, learner-centered education, and the integration of technology into career services. These results demonstrate that career guidance (CG) research is a nascent domain ripe for theoretical and methodological investigation. In summary, this study provides strategic insights into the development of career guidance scholarship and the adaptive development of career services in response to the demands of 21st-century education.